Begonia × marceloi (Begoniaceae) a new natural hybrid from submontane Atlantic Forest in São Paulo State, Brazil - Miranda, Marcelo Dias (Phytotaxa, 2026)
A new natural hybrid, Begonia × marceloi, is described from the State of São Paulo, Brazil and illustrated with photographs. This hybrid was found in submontane ombrophilous dense forest, in very humid places close to a watercourse. The leaf shape of the plant attracted attention because it was different from other species which occur in the region. Hybrid individuals were found living among Begonia spinibarbis, and close to Begonia lorenzii as well. After a detailed morphological study of the putative hybrid and its suspected parents it was possible to conclude that Begonia × marceloi is a natural hybrid between Begonia spinibarbis and Begonia lorenzii.